PENGARUH INFLASI, PENGELUARAN PEMERINTAH DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Yusra Mahzalena; Hijri Juliansyah (LPPM UNIMAL, 2019)
The purpose of this study was to determine the effect of inflation, Government spending, and exports on economic growth in Indonesia during 1990-2016. This study used time series data obtained from the Central Bureau of Statistics. The number of samples in this study was 27 years as the object of this research. This study used a Vector Autoregression Model (VAR) analysis tool with the help of Eviews 9 software. The results of the VAR analysis model showed that economic growth was insignificantly and positively influenced by its movements, inflation had a positive and insignificant effect on economic growth, and Government spending had a positive and insignificant effect on economic growth, while exports had a negative and insignificant effect on economic growth.